Utilisation of palm oil fibre cake biomass for magnetic nanoparticle biocomposites as adsorbents in Sasirangan liquid waste treatment - Syamsul Ma'arif Putra Ukhrawi; Iryanti Fatyasari Nata; Rinna Juwita; Ahmad Gazaly; Ismi Nur Karima; Angga Prasetya (Universitas Lambung Mangkurat, 2025)
Palm kernel fibre (fibre cake) is a waste product from the palm oil industry that has potential as a source of natural fibre. This study aims to utilise fibre cake to produce magnetic nanoparticle biocomposites as adsorbents for reducing the lead (Pb2+) content and Total Suspended Solids (TSS) in Sasirangan liquid waste. The research produced two types of biocomposites: one without amino groups (FCB-M) and one with amino groups (FCB-MH). Observations from Scanning Electron Microscopy (SEM) showed that magnetic nanoparticles had formed on the surface of the fibre cake. Treatment of palm oil fibres with NaOH restructured amorphous cellulose into crystalline cellulose, as indicated by a 30.25% increase in the Crystalinity Index (CrI) based on X-Ray Diffraction (XRD) analysis. The Pb²⁺ content absorbed by FCB and FCB-NH₂ was 97.84 mg/g and 101.82 mg/g, respectively, for 3 hours at pH 8. The modification of amino groups on the surface of the biocomposite resulted in a 164.85% increase in adsorption. The effectiveness of TSS reduction at pH 8 was 65.8% and 62.9% for FCB-M and FCB-MH, respectively.